PENGENDALIAN INDEKS HARGA SAHAM GABUNGAN UNTUK MEMACU INVESTASI MASYARAKAT - -, Suwarto - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2008)
ABSTRACT There are economic and non economic factors affect investment. Stimulus the activity of market securities called macro economic condition such as: gross national product ; circulation of money, inflate; stock of foreign exchange, balance of payment; interest and exchange rate. We need policy to espouse indicator of monetary economic FSR increasing of price index of stock grouping will motivate people to take investment of securities. Furthermore increasing price index of stock grouping. According to equation of y = 976114,21 - 351,693 X1 + 5.587,169 X2 – 0,208 X3 – 47,617 X4 + So, We can priority control : interest (X2); inflate (X2); exchange rate (X2); and circulation of money (X2); for increasing price index of stock grouping will motivate people to talk investment of securities. Keywords: price index, exchange rate, securities, investment, balance of payment